Astragalus Mongholicus: A review of its anti-fibrosis properties - Gong, Fengying; Qu, Rongmei; Li, Yongchun; Lv, Ying; Dai, Jingxing (Frontiers in Pharmacology, 2022)
Background: Fibrosis-related diseases (FRD) include cerebral fibrosis, pulmonary fibrosis, cardiac fibrosis, liver fibrosis, renal fibrosis, peritoneal fibrosis, etc. The effects of fibrosis can be severe, resulting in organ dysfunction, functional decline, and even organ failure, which can cause serious health problems. Aim： Currently, there is no effective modern medicine for anti-fibrosis in the clinics; however, Chinese medicine has a certain beneficial effect on treating such diseases. Astragalus Mongholicus (AM) has rich medicinal value, and its anti-fibrosis effect has been recently investigated. In recent years, more and more experimental studies have been conducted on the intervention of astragaloside IV (AS-IV), astragalus polysaccharide (APS), astragalus flavone, cycloastragalus alcohol, astragalus water extract and other pharmacological components in fibrosis-related diseases, attracting the interest of researchers. We aim to provide ideas for future research by summarizing recent research advances of AM in treating fibrosis-related diseases. Methods: A literature search was conducted from the core collections of electronic databases such as Baidu Literature, Sciencen.com, Google Scholar, PubMed, and Science Direct using the above keywords and the pharmacological and phytochemical details of the plant. Results: AM can be used to intervene in fibrosis-disease progression by regulating inflammation, oxidative stress, the immune system, and metabolism. Conclusion: AS-IV, APS, and astragalus flavone were studied and discussed in detail. These components have high potential anti-fibrosis activity. Overall, this review aims to gain insight into the AM’s role in treating fibro-related diseases.